تركيز الهيدروكربونات النفطية الكلية في المياه الجوفية للآبار القريبة من مصافي الجنوب في منطقة الشعيبة قضاء الزبير – مدينه البصرة جنوب العراق - يوسف الخفاجي باسم; مهدي يونس بثينة (University of Thi-Qar Journal of Science, 2016)
The present study comprise of the concentration of total dissolved and suspended petroleum hydrocarbons in the water of groundwater to eight wells, six of which (W1-W6) close to the refinery area and two (W7-W8) are far from the region (wells control) in the surrounding refineries south region (Al-Shiaba) Zubair - Basra, southern Iraq, water samples were collected seasonally from the autumn of 2015 until the summer of 2016.Concentrations of total petroleum hydrocarbons, were measured using fluorescence device, as the highest value recorded 35.91 μg /L in the well W1 in spring 2016 and the lowest value of 0.73 μg /L in the well W7 in summer 2016. The highest concentrations of petroleum hydrocarbons rates recorded outstanding in the water total 137.39 mg .g-1 dry weight in the first well W1 in spring 2016, while the lowest concentration of 9.89 mg .g-1 dry weight, in the well W8 during the summer 2016.